Modified powder, method for producing the same, and cosmetic comprising the same
Patent Information
- Application Number
- CN202311391870.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-10-25
AI Technical Summary
[0003]目前,常用的改性剂处理后的粉体要么疏水性良好,但润滑度不足,不够贴肤,要么润滑度良好,但无法达到超疏水的要求,不能同时满足疏水性和润滑度的要求
[0022]In this invention, a branched polysiloxane is used to modify the base powder. The branched polysiloxane can chemically react with the base powder, thereby fixing the branched polysiloxane to the surface of the base powder and forming a strong coating. At the same time, since the branched polysiloxane has abundant methyl and organosilicon branches, the surface of the resulting modified powder has a coating surface including abundant methyl and organosilicon branches, which makes the modified powder have excellent hydrophobicity, lubricity, skin adhesion and oil compatibility.
Smart Images

Figure CN117243855B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cosmetic technology, and in particular to a modified powder, a method for preparing the same, and cosmetics comprising the modified powder. Background Technology
[0002] In order for powders to be better applied in cosmetic formulations, they usually need to have good hydrophobicity.
[0003] Currently, powders treated with commonly used modifiers either have good hydrophobicity but insufficient lubricity and do not adhere well to the skin, or they have good lubricity but cannot meet the requirements of superhydrophobicity, and cannot simultaneously meet the requirements of hydrophobicity and lubricity. Summary of the Invention
[0004] Therefore, it is necessary to address the above problems by providing a modified powder, a method for preparing the modified powder, and a cosmetic product comprising the modified powder, wherein the modified powder has excellent hydrophobicity, lubricity, skin adhesion, and oil compatibility.
[0005] A modified powder, comprising a base powder and a branched polysiloxane coated on the surface of the base powder, wherein the branched polysiloxane has a structure consisting of four chain segments, denoted by M, D, W, and T, respectively, and the structural formula of the branched polysiloxane can be represented as M. a D b W c T d ;
[0006] Where M is [(CH3)3SiO 1 / 2 [(CH3)2SiO] chain segment, D is [R(CH3)SiO] chain segment, W is [R(CH3)SiO] chain segment, T is [(CH3)SiO] chain segment. 3 / 2 Let R be a chain segment, and a + b + c + d = 1, 0.01 ≤ a ≤ 0.5, 0.1 ≤ b ≤ 0.9, 0.01 ≤ c ≤ 0.8, 0 ≤ d ≤ 0.5, where R is selected from R. x and / or R y The R x For C2-C 10 alkyl group, wherein R y It is a triethoxysilyl group, x + y = 1, 0 ≤ x < 0.5, 0.5 ≤ y ≤ 1, where a, b, c, and d are the mass fractions of each chain segment in the branched polysiloxane, and x and y are the mass fractions of R. x and the R y The mass fraction in R.
[0007] In one embodiment, 0.01≤a≤0.2, 0.2≤b≤0.8, 0.05≤c≤0.5, 0≤d≤0.2;
[0008] And / or, 0≤x≤0.2, 0.8≤y≤1;
[0009] And / or, the R x It is a C4-C6 alkyl group.
[0010] In one embodiment, the branched polysiloxane has a molecular weight of 3000-6000;
[0011] And / or, the branched polysiloxane has a viscosity of 30 mm at 25°C. 2 / s-100mm 2 / s.
[0012] In one embodiment, the mass ratio of the base powder to the branched polysiloxane is 100:1-100:6.
[0013] In one embodiment, R is selected from triethoxysilyl group.
[0014] In one embodiment, the base powder is selected from at least one of titanium dioxide, iron oxide red, iron oxide black, iron oxide yellow, iron oxide brown, mica, sericite, synthetic fluorophlogopite, talc, boron nitride, hydroxyapatite, silica, kaolin, or hydrated silica.
[0015] A method for preparing the modified powder includes the following steps:
[0016] Provide basic powders;
[0017] The branched polysiloxane is dissolved in a solvent and added to the base powder under stirring to obtain a mixture;
[0018] The mixture was dried at 100℃-140℃ to obtain modified powder.
[0019] In one embodiment, the pH of the base powder is 5-10.
[0020] A cosmetic comprising the modified powder described above.
[0021] In one embodiment, the cosmetic is selected from color cosmetics.
[0022] In this invention, a branched polysiloxane is used to modify the base powder. The branched polysiloxane can chemically react with the base powder, thereby fixing the branched polysiloxane to the surface of the base powder and forming a strong coating. At the same time, since the branched polysiloxane has abundant methyl and organosilicon branches, the surface of the resulting modified powder has a coating surface including abundant methyl and organosilicon branches, which makes the modified powder have excellent hydrophobicity, lubricity, skin adhesion and oil compatibility.
[0023] Therefore, the modified powder obtained by the branched polysiloxane treatment has good hydrophobicity, smooth and soft surface, smooth and non-sticky feel, and good spreadability. When applied to cosmetics, it can exhibit excellent compatibility, dispersibility and stability in a variety of oils. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 This is a contact angle test diagram of the modified titanium dioxide in Example 1 of the present invention;
[0026] Figure 2 This is a contact angle test diagram of modified iron oxide red in Example 2 of the present invention. Detailed Implementation
[0027] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.
[0029] Currently, modifiers such as triethoxyoctylsilane and polydimethylsiloxane are commonly used to modify the surface of base powders, giving the modified base powders a certain degree of hydrophobicity. However, when using these modifiers to modify base powders, they cannot simultaneously provide excellent hydrophobicity, lubricity, and skin adhesion. For example, when using triethoxyoctylsilane to modify base powders, although the chemical coating on the surface of the base powder is good, the modified powder has poor lubricity and skin adhesion. When using polydimethylsiloxane to modify base powders, the modified powder has a certain degree of lubricity, but it is a physical coating, and the polydimethylsiloxane is not firmly attached to the surface of the base powder, and its grease compatibility is poor.
[0030] Therefore, the present invention provides a modified powder comprising a base powder and a branched polysiloxane coated on the surface of the base powder. The branched polysiloxane consists of four chain segments, which are represented by M, D, W, and T, respectively. The structural formula of the branched polysiloxane can be represented as M. a D b W c T d ;
[0031] Where M is [(CH3)3SiO 1 / 2 [(CH3)2SiO] chain segment, D is [R(CH3)SiO] chain segment, W is [R(CH3)SiO] chain segment, T is [(CH3)SiO] chain segment. 3 / 2 Let R be a chain segment, and a + b + c + d = 1, 0.01 ≤ a ≤ 0.5, 0.1 ≤ b ≤ 0.9, 0.01 ≤ c ≤ 0.8, 0 ≤ d ≤ 0.5, where R is selected from R. x and / or R y The R x For C2-C 10 alkyl group, wherein R y It is a triethoxysilyl group, x + y = 1, 0 ≤ x < 0.5, 0.5 ≤ y ≤ 1, where a, b, c, and d are the mass fractions of each chain segment in the branched polysiloxane, and x and y are the mass fractions of R. x and the R y The mass fraction in R.
[0032] In this invention, compared with common modifiers used for base powders, the branched polysiloxane has abundant branches. By chemically bonding with the surface of the base powder and coating it, a coating surface can be formed on the surface of the base powder, thereby improving the coating effect on the base powder.
[0033] Furthermore, the base powder is modified with branched polysiloxanes. These branched polysiloxanes can chemically react with the base powder, thereby fixing the branched polysiloxanes onto the surface of the base powder in a chemical coating form, forming a strong coating surface. Simultaneously, because the branched polysiloxanes have abundant methyl and organosilicon branches, the modified powder exhibits excellent hydrophobicity, lubricity, and skin-adhesion. The resulting modified powder, with its branched polysiloxane coating, possesses excellent hydrophobicity, lubricity, skin-adhesion, and oil compatibility.
[0034] Therefore, the modified powder obtained by the branched polysiloxane treatment has good hydrophobicity, smooth and soft surface, smooth and non-sticky feel, and good spreadability. When applied to cosmetics, it can exhibit excellent compatibility, dispersibility and stability in a variety of oils.
[0035] Specifically, the branched polysiloxane can form a partial or complete coating on the surface of the base powder. Preferably, when the branched polysiloxane forms a complete coating on the surface of the base powder, the modified powder has a core-shell structure, which can achieve a better coating effect.
[0036] Optionally, in the molecular structure of the branched polysiloxane, 0.01≤a≤0.2, 0.2≤b≤0.8, 0.05≤c≤0.5, and 0≤d≤0.2.
[0037] Optionally, 0 ≤ x ≤ 0.2, 0.8 ≤ y ≤ 1, thus increasing R in R y The content of [specific ingredient] further improves the hydrophobicity and oleocompatibility of the branched polysiloxane, and is also beneficial to enhancing the chemical coating effect.
[0038] Optional, R x The alkyl group is C4-C6, thereby further improving the hydrophobicity and oleophobicity of the branched polysiloxane.
[0039] Optionally, the branched polysiloxane has a molecular weight of 3000-6000, which helps to control the flowability and dispersibility of the branched polysiloxane in the foundation liquid and improve the coating effect on the base powder.
[0040] Optionally, the branched polysiloxane has a viscosity of 30 mm at 25°C. 2 / s-100mm 2 / s, and more preferably, the viscosity of the branched polysiloxane is 40 mm. 2 / s-70mm 2 / s, thereby enabling the branched polysiloxane to be better dispersed and flowed in the foundation liquid, further improving the coating effect on the base powder.
[0041] Optionally, the mass ratio of the base powder to the branched polysiloxane is 100:1-100:6, more preferably 100:2-100:4, which can achieve better coating effect, improve the hydrophobicity, lubricity and skin adhesion of the modified powder, and has high oil compatibility and a smooth and fluffy feel.
[0042] Optionally, R is preferably a combination of alkyl and triethoxysilyl, or R is preferably triethoxysilyl. Triethoxysilyl can also chemically bond with the surface of the base powder, so that the branched polysiloxane can be more firmly coated on the surface of the base powder, further forming a coating surface, thereby improving the hydrophobicity, lubricity, skin adhesion and oil compatibility of the modified powder.
[0043] Optionally, the base powder is selected from at least one of titanium dioxide, iron oxide red, iron oxide black, iron oxide yellow, iron oxide brown, mica, sericite, synthetic fluorophlogopite, talc, boron nitride, hydroxyapatite, silica, kaolin, or hydrated silica.
[0044] The present invention also provides a method for preparing the modified powder, comprising the following steps:
[0045] S1 provides the basic powder;
[0046] S2, the branched polysiloxane is dissolved in a solvent and added to the base powder under stirring to obtain a mixture;
[0047] S3, the mixture is dried at 100℃-140℃ to obtain modified powder.
[0048] In step S1, the pH of the base powder is preferably 5-10, and more preferably 7-8, which is beneficial to the subsequent modification treatment of the base powder by branched polysiloxane and improves the coating effect.
[0049] Specifically, since different types of base powders have different surface pH values, when the pH of the selected base powder is not within the above range, the pH of the base powder needs to be adjusted so that the pH of the base powder is 5-10, and more preferably 7-8.
[0050] Optionally, the pH of the base powder can be adjusted by using an acid or a base. For example, the acid can preferably be at least one of hydrochloric acid or acetic acid, and the base can preferably be at least one of sodium hydroxide or a 28% ammonia solution.
[0051] In step S2, the branched polysiloxane is dissolved in a solvent to form a branched polysiloxane solution, the solution is added to the base powder, and the mixture is stirred to obtain a mixture.
[0052] Optionally, the solvent for dissolving branched polysiloxanes is preferably at least one of isododecane or ethanol.
[0053] Optionally, the method of adding the branched polysiloxane solution to the base powder is not specifically limited, but dropwise addition is preferred. This is more conducive to promoting the uniformity of mixing between the branched polysiloxane and the base powder, so that the branched polysiloxane can more evenly coat the surface of the base powder, forming a more uniform coating surface, improving the coating effect, and thus improving the hydrophobicity, lubricity and skin adhesion of the modified powder.
[0054] Optionally, in the step of mixing to obtain the mixture, high-speed stirring can promote the uniformity of mixing between the branched polysiloxane and the base powder, and further improve the coating effect of the branched polysiloxane on the base powder.
[0055] In step S3, drying at 100℃-140℃ can activate the branched polysiloxane, promote the chemical bonding between the branched polysiloxane and the surface of the base powder, further enhance the coating effect of the branched polysiloxane, and facilitate the formation of the coating surface.
[0056] Optionally, the modified powder may be cooled after drying, and the cooling method is not specifically limited.
[0057] The present invention also provides a cosmetic comprising the modified powder described above. When the modified powder of the present invention is used in cosmetics, the modified powder exhibits excellent dispersibility and stability, and good compatibility with other components in the cosmetic, resulting in cosmetics with good spreadability, good skin adhesion, good skin feel, and stable quality.
[0058] In one embodiment, the cosmetic is preferably a color cosmetic, such as: foundation, loose powder, setting powder, concealer, lipstick, eyeshadow, lip pencil, eyebrow pencil, etc.
[0059] The modified powder and its preparation method, as well as cosmetics including the modified powder, will be further described below through specific embodiments.
[0060] Example 1
[0061] Take 100g of titanium dioxide with a particle size of 300nm and a pH of 6.5 and place it in a grinding pot. Provide a branched polysiloxane: triethoxysilyl ethyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYLPOLYDIMETHYLSILOXYETHYL DIMETHICONE), where a = 0.01, b = 0.8, c = 0.15, d = 0.04, x = 0, y = 1, molecular weight is 1000, and viscosity at 25℃ is 30mm. 2 / s. Dissolve and disperse 7g of branched polysiloxane in 7g of isododecane, and add it evenly dropwise into a grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, the modified titanium dioxide is obtained.
[0062] The hydrophobicity test results of the modified titanium dioxide in this embodiment are shown in Table 1.
[0063] Example 2
[0064] Take 100g of iron oxide red with a particle size of 250nm and a pH of 3.5 in a grinding pot, and add 28% ammonia solution dropwise to adjust the pH of the iron oxide red to 7.0. This provides a branched polysiloxane: triethoxysilyl ethyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYL POLYDIMETHYLSILOXYETHYLDIMETHICONE), where a = 0.2, b = 0.6, c = 0.2, d = 0, x = 0, y = 1, molecular weight is 3000, and viscosity at 25℃ is 51 mm. 2 / s. Dissolve and disperse 1g of branched polysiloxane in 1g of isododecane, and add it evenly dropwise into a grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, modified iron oxide red is obtained.
[0065] The hydrophobicity test results of the modified iron oxide red in this embodiment are shown in Table 1.
[0066] Example 3
[0067] Take 100g of ferric oxide yellow with a particle size of 300nm and a pH of 6.5 into a grinding pot, and provide a branched polysiloxane: triethoxysilyl ethyl polydimethylsiloxane ethylhexyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYL POLYDIMETHYLSILOXYETHYL HEXYL DIMETHICONE), where a = 0.1, b = 0.2, c = 0.5, d = 0.2, x = 0.1, y = 0.9, R x It is hexyl, with a molecular weight of 5000 and a viscosity of 68 mmHg at 25°C. 2 / s. Dissolve and disperse 6g of branched polysiloxane in 6g of isododecane, and add it evenly dropwise into a grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, the modified iron oxide yellow is obtained.
[0068] The hydrophobicity test results of the modified iron oxide yellow in this embodiment are shown in Table 1.
[0069] Example 4
[0070] Take 100g of iron oxide black with a particle size of 300nm and a pH of 6.8 and place it in a grinding pot. Provide a branched polysiloxane: triethoxysilyl ethyl polydimethylsiloxane ethylhexyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYL POLYDIMETHYLSILOXYETHYL HEXYL DIMETHICONE), where a = 0.1, b = 0.7, c = 0.05, d = 0.15, x = 0.2, y = 0.8, R x It is butyl, with a molecular weight of 8000 and a viscosity of 100 mm at 25°C. 2 / s. Dissolve and disperse 2g of branched polysiloxane in 2g of isododecane, and add it evenly dropwise into a grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, the modified iron oxide black is obtained.
[0071] The hydrophobicity test results of the modified iron oxide black in this embodiment are shown in Table 1.
[0072] Example 5
[0073] 100g of sericite with a particle size of 300nm and a pH of 6.5 was placed in a grinding pan to provide a branched polysiloxane: triethoxysilyl ethyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYLPOLYDIMETHYLSILOXYETHYL DIMETHICONE), wherein a = 0.1, b = 0.7, c = 0.1, d = 0.1, x = 0, y = 1, molecular weight is 1000, and viscosity at 25℃ is 30mm. 2 / s. Dissolve and disperse 3g of branched polysiloxane in 3g of isododecane, and add it evenly dropwise into a grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, modified sericite is obtained.
[0074] The hydrophobicity test results of the modified sericite in this embodiment are shown in Table 1.
[0075] Comparative Example 1
[0076] Take 100g of titanium dioxide with a particle size of 300nm and a pH of 5.5 and put it into a grinding pot. Provide polydimethylsiloxane, dissolve and disperse 3g of polydimethylsiloxane in 3g of isododecane, and add it evenly dropwise into the grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, the modified titanium dioxide is obtained.
[0077] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0078] Comparative Example 2
[0079] Take 100g of titanium dioxide with a particle size of 300nm and a pH of 5.5 and put it into a grinding pot. Provide triethoxyoctylsilane, dissolve and disperse 3g of triethoxyoctylsilane in 3g of isododecane, and add it evenly dropwise into the grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, the modified titanium dioxide is obtained.
[0080] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0081] Comparative Example 3
[0082] Take 100g of titanium dioxide with a particle size of 300nm and a pH of 5.5 and place it in a grinding pot. Provide a branched polysiloxane: triethoxysilyl ethyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYLPOLYDIMETHYLSILOXYETHYL DIMETHICONE), where a = 0.6, b = 0.3, c = 0.05, d = 0.05, x = 0, y = 1, molecular weight is 10000, and viscosity at 25℃ is 127 mm. 2 / s. Dissolve and disperse 3g of branched polysiloxane in 3g of isododecane, and add it evenly dropwise into a grinding pot. Stir and mix thoroughly at 20000r / min for 20s to obtain a mixture. Then place the mixture in an oven at 120℃ and heat and dry for 2 hours. After cooling, the modified titanium dioxide is obtained.
[0083] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0084] Comparative Example 4
[0085] The difference between Comparative Example 4 and Example 1 is that in the branched polysiloxane, a = 0.2, b = 0.05, c = 0.6, d = 0.15, the molecular weight is 900, and the viscosity at 25°C is 24 mm. 2 / s.
[0086] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0087] Comparative Example 5
[0088] The difference between Comparative Example 5 and Example 1 is that in the branched polysiloxane, a = 0.04, b = 0.95, c = 0.01, d = 0, the molecular weight is 1000, and the viscosity at 25°C is 31 mm. 2 / s.
[0089] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0090] Comparative Example 6
[0091] The difference between Comparative Example 6 and Example 1 is that in the branched polysiloxane, a = 0.16, b = 0.8, c = 0, d = 0.04, the molecular weight is 1000, and the viscosity at 25°C is 28 mm. 2 / s.
[0092] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0093] Comparative Example 7
[0094] The difference between Comparative Example 7 and Example 1 is that in the branched polysiloxane, a = 0.01, b = 0.14, c = 0.85, d = 0, the molecular weight is 1000, and the viscosity at 25°C is 32 mm. 2 / s.
[0095] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0096] Comparative Example 8
[0097] The difference between Comparative Example 8 and Example 1 is that in the branched polysiloxane, a = 0.01, b = 0.4, c = 0.04, d = 0.55, the molecular weight is 1000, and the viscosity at 25°C is 30 mm. 2 / s.
[0098] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0099] Comparative Example 9
[0100] The difference between Comparative Example 9 and Example 1 is that the branched polysiloxane is triethoxysilyl ethyl polydimethylsiloxane ethylhexyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYLPOLYDIMETHYLSILOXYETHYL HEXYL DIMETHICONE), where x = 0.6, y = 0.4, R xIt is octyl, with a molecular weight of 1000 and a viscosity of 32 mm at 25°C. 2 / s.
[0101] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0102] Comparative Example 10
[0103] The difference between Comparative Example 10 and Example 1 is that the branched polysiloxane is triethoxysilyl ethyl polydimethylsiloxane ethylhexyl polydimethylsiloxane (INCI name: TRIETHOXYSILYLETHYLPOLYDIMETHYLSILOXYETHYL HEXYL DIMETHICONE), where x = 0.6, y = 0.4, R x It is a dodecyl group with a molecular weight of 1000 and a viscosity of 31 mm at 25°C. 2 / s.
[0104] The hydrophobicity test results of the modified titanium dioxide in this comparative example are shown in Table 1.
[0105] Table 1
[0106]
[0107]
[0108] As shown in Table 1, the contact angles of the modified powders obtained in the embodiments of the present invention are all greater than 150°, indicating superhydrophobicity.
[0109] Application Example 1
[0110] The modified powder obtained in the embodiments of the present invention was used in the liquid foundation, and the liquid foundation formula is shown in Table 2.
[0111] Table 2
[0112]
[0113] Referring to Application Example 1, the modified titanium dioxide of Comparative Examples 1-10 was used in foundation liquid.
[0114] Thirty volunteers were selected as research subjects. After applying the foundation from Example 1 and Comparative Examples 1-10, respectively, the volunteers recorded and scored the effects on two aspects: skin adherence and smoothness. The scoring range was 0-10, with higher scores indicating better performance. The scores from all 30 volunteers for the same foundation were averaged. Scores of 8 ≤ N ≤ 10 were considered excellent in terms of skin adherence and smoothness; scores of 6 ≤ N < 8 were considered good; and scores of N < 6 were considered poor.
[0115] The statistical results of Application Example 1 and Application Comparative Examples 1-10 are shown in Table 3.
[0116] Table 3
[0117]
[0118] As can be seen from Application Example 1 in Table 3, the modified powder obtained by modifying the base powder with branched polysiloxane and applying the modified powder to the foundation liquid can achieve excellent lubricity and skin adhesion. This indicates that the branched polysiloxane forms a chemical coating surface by chemically bonding with the surface of the base powder, thereby achieving excellent coating effect. Therefore, the modified powder has abundant methyl and organosilicon branches on its surface, which makes the modified powder have excellent lubricity and skin adhesion.
[0119] As can be seen from Comparative Examples 1-10 in Table 3, modified powders obtained by using conventional powder modifiers or other branched polysiloxanes have poor coating effects. As a result, when the modified powders are applied to liquid foundation, the lubricity and skin adhesion of the liquid foundation are reduced.
[0120] Application Example 2
[0121] The modified powder obtained in the embodiments of the present invention was used in eyeshadow, and the eyeshadow formula is shown in Table 4.
[0122] Table 4
[0123]
[0124] Referring to Application Example 1 and Application Comparative Examples 1-10, Application Example 2 and Application Comparative Examples 11-20 were set up. The statistical results of Application Example 2 and Application Comparative Examples 11-20 are shown in Table 5.
[0125] Table 5
[0126]
[0127]
[0128] Application Example 3
[0129] The modified powder obtained in the embodiments of the present invention is used in lipstick, and the lipstick formula is shown in Table 6.
[0130] Table 6
[0131]
[0132] Referring to Application Example 1 and Application Comparative Examples 1-10, Application Example 3 and Application Comparative Examples 21-30 were set up. The statistical results of Application Example 3 and Application Comparative Examples 21-30 are shown in Table 7.
[0133] Table 7
[0134]
[0135]
[0136] As can be seen from Application Examples 2 and 3 in Tables 5 and 7, the modified powder can still achieve excellent lubricity and skin adhesion when applied to eyeshadow and lipstick, indicating that the modified powder of the present invention can be applied to a variety of makeup formulations and has excellent lubricity and skin adhesion in a variety of makeup formulations.
[0137] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0138] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A modified powder, characterized in that, The modified powder comprises a base powder and a branched polysiloxane coated on the surface of the base powder. The branched polysiloxane consists of four chain segments, which are represented by M, D, W, and T, respectively. The structural formula of the branched polysiloxane can be represented as M. a D b W c T d ; Where M is [(CH3)3SiO 1 / 2 [(CH3)2SiO] chain segment, D is [R(CH3)SiO] chain segment, W is [R(CH3)SiO] chain segment, T is [(CH3)SiO] chain segment. 3 / 2 Let R be a chain segment, and a + b + c + d = 1, 0.01 ≤ a ≤ 0.2, 0.2 ≤ b ≤ 0.8, 0.05 ≤ c ≤ 0.5, 0 < d ≤ 0.2, and R be selected from R. x and / or R y The R x R is a C4-C6 alkyl group. y The polysiloxane is a triethoxysilyl compound, x + y = 1, 0 ≤ x ≤ 0.2, 0.8 ≤ y ≤ 1, where a, b, c, and d are the mass fractions of each chain segment in the branched polysiloxane, and x and y are the mass fractions of R. x and the R y The mass fraction in R; the contact angle of the modified powder is greater than 150° in the hydrophobicity test; The base powder is selected from at least one of titanium dioxide, iron oxide red, iron oxide black, iron oxide yellow, iron oxide brown, mica, sericite, synthetic fluorophlogopite, talc, boron nitride, hydroxyapatite, silica, kaolin, or hydrated silica.
2. The modified powder according to claim 1, characterized in that, The molecular weight of the branched polysiloxane is 3000-6000; And / or, the branched polysiloxane has a viscosity of 30 mm at 25°C. 2 / s-100mm 2 / s.
3. The modified powder according to any one of claims 1-2, characterized in that, The mass ratio of the base powder to the branched polysiloxane is 100:1-100:
6.
4. The modified powder according to claim 1, characterized in that, R is selected from triethoxysilyl group.
5. A method for preparing the modified powder according to any one of claims 1-4, characterized in that, Includes the following steps: Provide basic powders; The branched polysiloxane is dissolved in a solvent and added to the base powder under stirring to obtain a mixture; The mixture was dried at 100℃-140℃ to obtain modified powder.
6. The method for preparing the modified powder according to claim 5, characterized in that, The pH of the base powder is 5-10.
7. A cosmetic comprising the modified powder according to any one of claims 1-4.
8. The cosmetic product according to claim 7, characterized in that, The cosmetics mentioned are selected from color cosmetics.
Citation Information
Patent Citations
Cosmetic
JP2004231609A
Powder cosmetic
JP2007022951A